2023
DOI: 10.3389/fsurg.2023.1076848
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of efficacy and safety of non-ablative 1927 nm fractional thulium fiber laser in Asian skin photoaging

Abstract: Background and ObjectivePhotoaging manifests as deeper wrinkles and larger pores. It has been tried to rejuvenate photoaging skin using a variety of lasers, including fractionated lasers, which are a popular photorejuvenation treatment. A new breakthrough for skin rejuvenation is the 1927 nm fractional thulium fiber laser (FTL), a laser and light-based treatment option. Clinical data regarding the FTL for treating photoaging are limited despite its effectiveness and safety. This study is aim to evaluate FTL' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They found that the Q-switched Nd:YAG laser led to faster healing and greater patient satisfaction, although the incidence of PIH was similar between the 2 lasers. Conversely, Li and colleagues 49 conducted a prospective clinical trial on skin photoaging using a 1,927-nm fractional thulium fiber laser. Their results showed significant improvements in epidermal thickness and dermal density, with transient adverse effects, such as edema, erythema, dryness, and desquamation reported.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the Q-switched Nd:YAG laser led to faster healing and greater patient satisfaction, although the incidence of PIH was similar between the 2 lasers. Conversely, Li and colleagues 49 conducted a prospective clinical trial on skin photoaging using a 1,927-nm fractional thulium fiber laser. Their results showed significant improvements in epidermal thickness and dermal density, with transient adverse effects, such as edema, erythema, dryness, and desquamation reported.…”
Section: Resultsmentioning
confidence: 99%